2014
DOI: 10.1128/aem.01409-14
|View full text |Cite
|
Sign up to set email alerts
|

Identification of Different Bartonella Species in the Cattle Tail Louse (Haematopinus quadripertusus) and in Cattle Blood

Abstract: bBartonella spp. are worldwide-distributed facultative intracellular bacteria that exhibit an immense genomic diversity across mammal and arthropod hosts. The occurrence of cattle-associated Bartonella species was investigated in the cattle tail louse Haematopinus quadripertusus and in dairy cattle blood from Israel. Lice were collected from cattle from two dairy farms during summer 2011, and both lice and cow blood samples were collected from additional seven farms during the successive winter. The lice were … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
32
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 29 publications
(34 citation statements)
references
References 43 publications
1
32
0
Order By: Relevance
“…Currently, there is scarce information about the vectors responsible for the transmission of Bartonella in cows, although lice (Haematopinus quadripertusus), ticks (Rhipicephalus microplus), or biting flies (Hippobosca and Haematobia spp.) have been involved as potential vectors (22,35,36,37). In our study, ticks were found on the studied animals (data not shown), although they could not be tested for Bartonella.…”
Section: Discussionmentioning
confidence: 83%
“…Currently, there is scarce information about the vectors responsible for the transmission of Bartonella in cows, although lice (Haematopinus quadripertusus), ticks (Rhipicephalus microplus), or biting flies (Hippobosca and Haematobia spp.) have been involved as potential vectors (22,35,36,37). In our study, ticks were found on the studied animals (data not shown), although they could not be tested for Bartonella.…”
Section: Discussionmentioning
confidence: 83%
“…Indeed, the latter phenomena have been already reported in Bartonella species from wild rodents (Harrus et al, 2009;Paziewska et al, 2011), cattle (Gutiérrez et al, 2014) and bats (Bai et al, 2015). These distinct possibilities reinforce the great challenge on Bartonella identification based on direct molecular detection in blood, tissue or ectoparasite samples (Gutiérrez et al, 2014;Kosoy et al, 2017). Although the multiple loci sequencing approach was attempted in the present study for a better understanding of sequences phylogenetic positioning and possible recombinant events and/ or infection by multiple Bartonella species (Kosoy et al, 2017), the unique positive sample (#62) in cPCR assays was negative in PCR targeting additional genes (rpoB and groEL), thus precluding to solve this issue.…”
Section: Discussionmentioning
confidence: 88%
“…Therefore, it suggests that Bartonella and haemoplasma species detected in S. caffer in the present study may be potentially transmitted by these tick species. In addition to possible role of ticks in the transmission of Bartonella, several studies have reported the isolation or molecular detection of Bartonella species in other bloodsucking arthropods associated with wild and domestic ruminants (Chung et al, 2004;Dehio et al, 2004;Halos et al, 2004;Duodu et al, 2013;Gutiérrez et al, 2014). Regarding the haemoplasma transmission, few studies have accessed the mechanisms of transmission by arthropod vectors.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…By similarity with the epidemiology of Bartonella henselae [13], Bartonella bacilliformis and Bartonella quintana [9], it is suspected that the transmission between reservoirs is ensured horizontally by a blood-suckling arthropod [22]. B. bovis DNA has already been amplified from biting flies (Haematobia sp., Lipoptena cervi), cattle tail louse and ticks [4,10,14,15,18,21,22,33,38]. Domestic felids and canids bites have also been suspected for B. henselae transmission [19].…”
Section: Introductionmentioning
confidence: 98%